Temozolomide and Pituitary Tumors: Current Understanding, Unresolved Issues, and Future Directions - Syro, Luis V.; Rotondo, Fabio; Camargo, Mauricio; Ortiz, Leon D.; Serna, Carlos A.; Kovacs, Kalman (Frontiers in Endocrinology, 2018)
Temozolomide, an alkylating agent, initially used in the treatment of gliomas was expanded to include pituitary tumors in 2006. After twelve years of use, temozolomide has shown a notable advancement in pituitary tumor treatment with a remarkable improvement rate in the 5-year overall survival and 5-year progression free survival in both aggressive pituitary adenomas and pituitary carcinomas. In this paper, we review the mechanism of action of temozolomide as alkylating agent, its interaction with DNA repair systems, therapeutic effects in pituitary tumors, unresolved issues, and future directions relating to new possibilities of targeted therapy.